2008
DOI: 10.1002/pat.1229
|View full text |Cite
|
Sign up to set email alerts
|

Migration and surface modification in polypropylene (PP)/polyhedral oligomeric silsequioxane (POSS) nanocomposites

Abstract: This paper reports on the migration of POSS-based nanocomposites both by annealing the melt and by heating the solid blend in the microwave oven. The migration proceeds to all surfaces of the sample as verified by ATR-FTIR spectra of the bottom and top surfaces. Concentrations of POSS on the surface, exceeding 50%, are obtained. Polarity of the matrix increases POSS migration. During annealing at 190-C, a sublimation of POSS from the upper surface occurs. In air, sublimation is decreased by oxidizing the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 53 publications
1
28
1
1
Order By: Relevance
“…This is most likely due to POSS nanocages migrating to the top of the surface after solvent evaporation [37]. POSS-PCU-FS displayed a ridge-like appearance on its surface.…”
Section: Resultsmentioning
confidence: 99%
“…This is most likely due to POSS nanocages migrating to the top of the surface after solvent evaporation [37]. POSS-PCU-FS displayed a ridge-like appearance on its surface.…”
Section: Resultsmentioning
confidence: 99%
“…The organic pendent groups can be designed to achieve the desired affinity with the host polymeric matrix [1,2]. Using POSS in polymer based nanocomposites is a promising issue for the design 561 Structure-properties relationships of polyhedral oligomeric silsesquioxane (POSS) filled PS nanocomposites of materials with high-performance in several applications [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] such as low-dielectric applications [6], biomaterials for cardiovascular [14] and dental implants [16], organic solar cells [17], flame resistant nanocomposites [18,19], optical limiting [20], etc. An important feature of the POSS formulation is their one-pot preparation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…the POSS loading decreases the matrix shear viscosity [21,22]. Moreover, a prolonged thermal treatment of the POSS polymerbased systems, results in migration of POSS molecules to the polymer matrix surface and to the formation of a thin protective POSS rich charred layer [19]. The fundamental understanding of the structureproperties relationships is of utmost importance when developing further applications of the POSS molecules as nanofillers in conventional polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the desorption of water during DMTA testing can lead to two peaks, since type 1 bound water can dissipate from the matrix first due to lower activation energy, leaving type 2 bound water which requires higher temperatures for desorption. It has been observed that in some instances POSS bearing aliphatic substituents have migrated to the sample surface of polymer blends and dramatically increase the hydrophobicity of the nanocomposites. However, the prereaction of the POSS with one component of the blend prior to incorporation makes it less likely that the POSS is drawn to the surface of the resin, since its mobility will be severely restricted.…”
Section: Resultsmentioning
confidence: 99%